Population-based study of morbidity risk associated with pathological complete response after chemoradiotherapy for rectal cancer. Issue 1 (17th October 2019) - van der Sluis, F J; Couwenberg, A M; de Bock, G H; Intven, M P W; Reerink, O; van Leeuwen, B L; van Westreenen, H L
Abstract: Background: Neoadjuvant chemoradiotherapy (nCRT) for locally advanced rectal cancer may induce a pathological complete response (pCR) but increase surgical morbidity due to radiation-induced fibrosis. In this study the association between pCR and postoperative surgical morbidity was investigated. Methods: Patients in the Netherlands with rectal cancer who underwent nCRT followed by total mesorectal excision between 2009 and 2017 were included. Data were stratified into patients who underwent resection with creation of a primary anastomosis and those who had a permanent stoma procedure. The association between pCR and postoperative morbidity was investigated in univariable and multivariable logistic regression analyses. Results: pCR was observed in 976 (12·2 per cent) of 8003 patients. In 3472 patients who had a primary anastomosis, the presence of pCR was significantly associated with surgical complications (122 of 443 (27·5 per cent) versus 598 of 3029 (19·7 per cent) in those without pCR) and anastomotic leak (35 of 443 (7·9 per cent) versus 173 of 3029 (5·7 per cent) respectively). Multivariable analysis also showed associations between pCR and surgical complications (adjusted odds ratio (OR) 1·53, 95 per cent c.i. 1·22 to 1·92) and pCR and anastomotic leak (adjusted OR 1·41, 1·03 to 2·05). Of 4531 patients with a permanent stoma, surgical complications were observed in 120 (22·5 per cent) of 533 patients with a pCR, compared with 798 (20·0 per cent) of 3998 patients with no pCR (adjusted OR 1·17, 0·94 to 1·46). Conclusion: Patients with a pCR in whom an anastomosis was created were at increased risk of developing an anastomotic leak. Graphical Abstract: This study aimed to clarify the relationship between pathological response to neoadjuvant chemoradiotherapy and surgical complications. To do this, surgical complication rates were investigated in a nationwide population-based study. More leaks